The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3641980
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric tunability transition in Ba0.6Sr0.4TiO3-based capacitors

Abstract: Dielectric properties of Au/Ba0.6Sr0.4TiO3/La1.1Sr0.9NiO4 (Au/BST/LSNO) thin film capacitors were investigated versus excitation frequency and dc bias voltage. At low frequencies, Au/BST/LSNO capacitors exhibited a usual positive tunability [i.e., C(0V) > C(V)], while an unexpected negative tunable behavior appeared at higher frequencies. On the basis of the dielectric tunable theory and equivalent electrical circuits, a model describing the dielectric tunability of Au/BST/LSNO capacitors is proposed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Based on previous literature, it appears that a suitable equivalent circuit for the epitaxial PZT films should include at least the following elements: a Schottky type capacitance associated with the electrode interfaces; a parallel R-C connection associated with the ferroelectric volume; a resistance associated with the electrodes. [39][40][41] Here, we show that the above mentioned equivalent circuit can be generalized and used to simulate the frequency dependence of impedance in the case of epitaxial films of BTO and Pb(Zr 0.2 Ti 0.8 )O 3 (PZT), with different structural orientations and with different metals as electrodes. Furthermore, it is shown that the equivalent circuit of a capacitor based on epitaxial ferroelectric film can be reduced to a simple R-C serial connection, in contrast to the parallel R-C connections used for ceramics.…”
Section: Introductionmentioning
confidence: 94%
“…Based on previous literature, it appears that a suitable equivalent circuit for the epitaxial PZT films should include at least the following elements: a Schottky type capacitance associated with the electrode interfaces; a parallel R-C connection associated with the ferroelectric volume; a resistance associated with the electrodes. [39][40][41] Here, we show that the above mentioned equivalent circuit can be generalized and used to simulate the frequency dependence of impedance in the case of epitaxial films of BTO and Pb(Zr 0.2 Ti 0.8 )O 3 (PZT), with different structural orientations and with different metals as electrodes. Furthermore, it is shown that the equivalent circuit of a capacitor based on epitaxial ferroelectric film can be reduced to a simple R-C serial connection, in contrast to the parallel R-C connections used for ceramics.…”
Section: Introductionmentioning
confidence: 94%
“…Barium strontium titanate (BST), as the material for nonlinear capacitors, exhibits high permittivity, high tunability and low dielectric loss at room temperature and in the microwave frequency range [1]. High quality BST films and capacitors have been prepared, and their electrical properties have also been investigated [2][3][4][5][6]. Since BST has a cubic crystal structure, BST films have been deposited on cubic crystal substrates such as MgO and SrTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Mostly deposited by PVD or PLD [1], alternative processes like sol-gel or metal oxide decomposition (MOD) are growing since a decade because of their low cost production [2][3][4] and more recently because of their ability to coat complex shapes (3D) [5]. To date, film densification and crack issues are the common technological bottle-necks for further improvements [6].…”
Section: Introductionmentioning
confidence: 99%